Statins: More than Cholesterol Reduction (Res Medica, 2014)
This article contains information from a talk given by the author at the RMS on 14/01/03, entitled: Statins and Immuno-modulation: A New Frontier. Statins represent one of the major successes of cardiology in the secondary prevention of coronary artery disease. This article attempts to understand the very molecule which makes many quake in their boots, cholesterol, and how basic science research continues to find novel methods in which statin therapy can participate.